1983
DOI: 10.1523/jneurosci.03-01-00145.1983
|View full text |Cite
|
Sign up to set email alerts
|

Protection of opiate receptors in NG108-15 against modification by N- ethylmaleimide

Abstract: Two different -SH groups associated with the opiate receptors of the mouse neuroblastoma X rat glioma hybrid NG108-15 have been identified. Modification of these by N-ethylmaleimide (NEM) (presumed to be via alkylation) or by para-chloromercuribenzoic acid (presumed to be via formation of mercury adducts) decreases the binding of both opiate agonists and antagonists to these receptors. Agonist binding is more sensitive than antagonist binding to modification by NEM. Losses in antagonist binding are accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…clase (17)(18)(19)(20). In sharp contrast, MalNEt has been found to ie results are in accord with our prior evidence that Malstabilize ternary complexes of agonist-p8-adrenergic recepdoes not modify the rates of association or dissociation tors-nucleotide-binding protein, and to slow the dissociation e antagonist [3H]QNB to or from either Ml or M2 recepof 8-adrenergic agonists (26,27).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…clase (17)(18)(19)(20). In sharp contrast, MalNEt has been found to ie results are in accord with our prior evidence that Malstabilize ternary complexes of agonist-p8-adrenergic recepdoes not modify the rates of association or dissociation tors-nucleotide-binding protein, and to slow the dissociation e antagonist [3H]QNB to or from either Ml or M2 recepof 8-adrenergic agonists (26,27).…”
supporting
confidence: 87%
“…Parallel effects of p[NH]ppG and MalNEt also have been noted for certain a-adrenoreceptors, dopamine receptors, opiate receptors, and other receptors (17)(18)(19)(20), all of which are believed to act via the attenuation of adenylate cyclase (11).…”
mentioning
confidence: 90%
“…1, NEM treatment of NG108-15 membranes almost completely abolishes adenylate cyclase activity and, under the conditions used, has little effect on opiate binding to receptors. As shown by others [12,13], NaCI protects opiate-binding sites from inactivation with NEM and in our experiments was found to be necessary to ensure selective impairment of adenylate cyclase only. Inclusion of opiate ligands (either agonists or antagonists) gave only a slight further protection of binding sites and was not generally deemed necessary in our experiments.…”
Section: Preparation Of Nem Membranessupporting
confidence: 83%
“…The results suggested that the agonists became tethered to the receptor via a mixed disulfide linkage that was in the vicinity of the receptor binding site. Other studies provided evidence that NEM affected opioid agonist binding by at least two mechanisms, direct inhibition (as mentioned above) and indirect inhibition due to uncoupling of receptors from G proteins (14,15).…”
mentioning
confidence: 93%
“…The results suggested that the agonists became tethered to the receptor via a mixed disulfide linkage that was in the vicinity of the receptor binding site. Other studies provided evidence that NEM affected opioid agonist binding by at least two mechanisms, direct inhibition (as mentioned above) and indirect inhibition due to uncoupling of receptors from G proteins (14,15).Several other, but not all, G protein-coupled receptors are also sensitive to sulfhydryl reagents. Susceptible receptors include the thyrotropin-releasing hormone (16), D1 and D2 dopamine (17, 18), substance P (19), ␣1 and ␣2 adrenoreceptor (20), platelet-activating factor (21), leukotriene B 4 (22), vasopressin (23), follicle-stimulating hormone (24), and cannabinoid receptors (25).…”
mentioning
confidence: 94%